Soil reinforcement potential of multifunctional crop plants on arable and non-arable tropical soils - Michael O. Adu; Peter B. Obour; Francis Kumi; Emmanuel Arthur; Paul A. Asare; Eric Oppong Danso; Samuel A. Banafo; Kwabena A. Sanleri; Hygienus Godswill; Kofi Atiah; Kwadwo K. Amoah; Joel B.K. Asiedu; et al. (Geoderma)
Root systems of grasses provide cost-effective, sustainable solution for soil stabilization, yet this potential in the roots of common arable crops remains largely unexplored. The objectives were to (i) evaluate the root tensile strength (Tr) of common arable crops (maize and sorghum) and a fodder plant (Napier grass) to assess their potential contribution to soil reinforcement, compared to vetiver grass, and (ii) assess the contribution of these crop plants to soil shear strength across different soil types and depths. A total of 48 soil columns measuring 70 cm height × 25 cm diameter (3 soil types × 4 crops × 4 replicates) were used for the experiment. The soils included two arable sandy loams and a sea sand. Root traits, including total root length (TRL), root length density (RLD), Tr, root area ratio (RAR), and root cohesion (Cr), were evaluated in addition to soil shear strength. Power law equations were fitted for Tr-root diameter relationships, and correlation analyses examined the relationship between soil shear strength and root variables. Multiple regression models were used to quantify the contribution of various root traits to the variation in soil shear strength. There were significant differences in Tr among crop plants, with Napier and vetiver grasses displaying the most robust roots. Soil columns planted with crops exhibited 45-80% higher mean soil shear strength than uncultivated soils, depending on the crop species, with Napier grass showing the highest values (63.99 ± 36.86 kPa). The plants grown in arable soils showed higher RAR and Cr in the uppermost soil layer and higher Tr values. Root traits explained 20–65 % of the variability in soil shear strength, with a positive linear relationship, and the contribution of these traits was more pronounced in arable soils (43–50 %) than in sea sand (21 %). The RLD was the main driver of soil shear strength, with the order of contribution to soil strength being RLD > RAR > TRL > root volume > Cr. Therefore, roots of common crops, mainly Napier grass and maize, can enhance soil shear strength, emphasising the potential of these plants for bioengineering applications, but tailored approaches based on specific soil types, crop species, and soil depths are vital.